化简(sina)^2*tana 2sina*cosa (cosa)^2*cota
1个回答
sin²AtanA2sinAcosAcos²AcotA
=2sin³Acos³A
=(sin³2A)/4
相关问题
sin^2 a*tana+cos^2*cota+2sina*cosa,化简
化简sina/|(sina)|+|cosa|/(cosa)+tana/|(tana)|
函数化简sinA/(1-cotA)+cosA/(1-tanA)
化简tana(cosa-sina)+sina(sina+tana)/1+cosa
若sina+cosa=2,则tana+cota=
已知(1+tana)/(1-tana)=3,则[(sina+cosa)^2-1]/(cota-sina*cosa)=?
求证:(cosA/(tanA/2-cotA/2))=-1/2*sinA
[(sina+cosa)^2-(sina-cosa)^2]/[tana-sina*cosa]
已知sina+cosa=1/2,求sina-cosa和tana+cota的值
化简(1+sina+cosa)(sina/2-cosa/2)/√(2+2cosA)